The financial performance's positive element in legislation of Spain - Aldeia, Susana (2020)
This paper aims to understand how Spain’s business law approaches the companies financial performance’s positive element. For this purpose, the study analyses the most pertinent business legislation, to identify legal dispositions, national, and international ones, that deals with the income concept. Internationally, it examines the International Accounting Standards (IAS) and the Conceptual Framework of the International Accounting Standard Board (IASB). In national domains, it analyses the Commerce Code (CC), the national accounting rules, and the corporate income tax law (CIT). The results show that, in order to European accounting harmonization, Spain adopts international accounting rules. In the internal domains, the business legislator was extensive because it expressly established the concept of income, not only in accounting law but also in commerce law. In the tax dimensions, the lawmaker assumes the concept implicitly when accepts the accounting profit as the bases for legal person's income tax determination. This research highpoint the Spanish practice in the process of economic concepts' business national laws incorporation. States can see Spain's knowledge. It keeps them resources and time. Although the relevance of the search, it treats only the Spanish experience.